(untitled) (Bangladesh Journal of Microbiology, 2020)
Electrogenic bacteria are able to transfer electrons to extracellular electron acceptors as well as can be used in devices like bioelectrochemical systems (BES). This study was focused to produce electricity from wastewater using microbial fuel cell and find out potential electrogenic bacteria from liquid tannery wastes. After power generation study, six isolates were screened as potential electrogenic bacteria. Of them, two potential bacteria were identified based on their morphological and biochemical characteristics and confirmed by phylogenetic analysis based on 16S rRNA gene sequence. We also investigated the effect of anode surface area on electricity generation in the microbial fuel cells and found that the surface area had positive impact on electricity generation. Bangladesh J Microbiol, Volume 37 Number 1 June 2020, pp 23-27